Liberia : Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria, Augmentation of Access, and Extension of the Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Liberia's Fifth and Sixth Reviews Under the Extended Credit Facility (ECF) Arrangement, Request for Waivers of Nonobservance of Performance Criteria, Augmentation of Access, and Extension of the Arrangement. Two end-December 2015 and three end-June performance criteria were missed. Two out of nine structural benchmarks for the fifth review were met, while three were completed late. Three out of five structural benchmarks for the sixth review were met. The IMF staff supports the completion of the fifth and sixth reviews and the authorities' requests for waivers of nonobservance of performance criteria, augmentation of ECF access, and extension of the ECF arrangement.